JOURNAL OF GOVERNMENT & POLITICS : Homophily and Organizational Identification towards Organizational Commitment and Organizational Justice among Male and Female office Workers in Iligan City - Odessa May D. Escalona, Anna patricia T Canono (FISIPOL UMY, 2016)
The study of identification within the organizational setting has highlighted various factors that may contribute significant changes, either positively or negatively, to the commitment and perception of fairness of employees.